2014
DOI: 10.4238/2014.may.9.12
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in TAP1 expression levels in newborn to weaning piglets, and its association with Escherichia coli F18 resistance

Abstract: ABSTRACT. The transporter associated with antigen processing (TAP) transports peptides from the cytosol into the endoplasmic reticulum for subsequent loading onto the major histocompatibility complex (MHC) class I molecules. This study showed the dynamic changes in the TAP1 expression level in newborn to weaning piglets. Tissue expression profiles revealed that the TAP1 gene was expressed at low levels in all tissues, and the expression levels were relatively higher in the lung, spleen, lymph, and thymus; furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…TAP1 plays a significant role in immune responses because of its increased expression level after infection by viruses and bacteria. Zhao et al (2014) analyzed TAP1 mRNA relative expression levels in 11 tissues from resistant and susceptible phenotypes, and found that the G729A mutation of TAP1 had a significant effect on TAP1 mRNA expression, with high expression possibly conferring resistance against E. coli F18, which confirms that the TAP1 gene plays an important role in E. coli F18 resistance (Wang et al, 2014). These results are also in agreement with Bao et al (2012).…”
Section: Polymorphism Of the Tap1 Genesupporting
confidence: 76%
“…TAP1 plays a significant role in immune responses because of its increased expression level after infection by viruses and bacteria. Zhao et al (2014) analyzed TAP1 mRNA relative expression levels in 11 tissues from resistant and susceptible phenotypes, and found that the G729A mutation of TAP1 had a significant effect on TAP1 mRNA expression, with high expression possibly conferring resistance against E. coli F18, which confirms that the TAP1 gene plays an important role in E. coli F18 resistance (Wang et al, 2014). These results are also in agreement with Bao et al (2012).…”
Section: Polymorphism Of the Tap1 Genesupporting
confidence: 76%
“…Uthe et al [9] found the TAP1 gene might play an important role in Salmonella resistance. Wang [10] et al analyzed dynamic changes in TAP1 expression levels in newborn to weaning piglets, and its association with Escherichia coli F18 resistance. The Sutai pig, which was generated by crossing Duroc pigs with Taihu pigs, is a high-quality and lean-meat breed.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we identified the differential expression of the FUT2 , FUT3 , TLR5 , TAP2 , IL1β genes in the duodenum, indicating that these genes probably play a crucial role in the resistance to E. coli F18. Our previous studies concentrated on the relationship of immune gene expression and E. coli F18 resistance in pigs [ 4 , 5 , 6 , 7 , 8 ], only a few reports directly on receptor formation showing the effect of the α(1,2) fucosyltransferase 1 ( FUT1 ) gene M307 G/A mutation on the adhesion of E. coli F18 to pig intestinal epithelial cells [ 9 ], but its polymorphism distribution in more than 20 Chinese local pig breeds and wild boar population is extremely skewed [ 10 , 11 , 12 ]. The smallest antigenic determinant of the E. coli F18 receptor is the type 1 H-antigen of the ABO blood group antigens [ 13 ].…”
Section: Introductionmentioning
confidence: 99%